Lineamientos pedagógicos para la utilización de dispositivos móviles en los estudiantes del nivel de educación básica - Cevallos Tapia , María José (2025)
The research focused on the issue arising from the absence of pedagogical guidelines to orient the use of mobile devices in basic education, a situation that led to disorganized practices and negative effects on students’ attention, self-regulation, and academic performance. In response to this problem, the general objective was to propose pedagogical guidelines to regulate and optimize the use of mobile devices as didactic resources within the school context. The study was conducted under a qualitative approach with an explanatory design, applying the inductive– deductive method and grounded theory, which facilitated the construction of emerging categories based on the collected data. The key informants consisted of three teachers from eighth grade, two from ninth grade, and two from tenth grade of the upper basic level, along with two educational technology specialists from the “Manuel de Jesús Calle” Basic Education School. Data collection techniques included a semi-structured interview, applied through a guide of open-ended questions, and non-participant observation. The results indicated that when mobile devices are integrated into pedagogical planning, they energize lessons, increase student motivation, strengthen content comprehension, and support the development of digital competencies. However, unregulated use generates distractions, inequalities in access, and risks of misuse. The specialists emphasized the need for institutional protocols, continuous teacher training, and shared responsibility with families. In conclusion, pedagogical guidelines were designed to provide an organized and contextualized framework that transforms mobile devices into tools for educational innovation, promoting meaningful, inclusive, and sustainable learning in basic education.